Report on the Beveridge proposals
1943-01-19 1943 1940s 20 pages 8. National Debt Service. Next, we shall be faced with a National Debt of the order at any rate of £20,000 million, and the interest alone on this sum, without taking into account the desirability of a sinking fund for its reduction, will be a very heavy burden greatly in excess of anything we have previously been called upon to bear. Again, Britain and the U.S.A. may, indeed almost certainly will, have to find large sums by way of grants and loans to feed and rebuild the overrun countries. After meeting these charges and commitments and the normal expenditure of the State to which we are already committed there will be a number of new claims on the national purse for education, housing, agriculture, Colonial development, roads, and much else besides. It will be necessary to determine their order of priority including such of the Beveridge proposals as may be approved. In view of the great destruction due to the War, housing must have a high place in the list. This item alone may make a call on capital financial resources of somewhere between £1,000,000,000 and £1,500,000,000 over the immediate post-war years. 12. In the light of all these factors, many of which involve expenditure the amount of which is unpredictable, we are asked to consider the Beveridge Report and to indicate how far we can go along the road of Social Insurance and to what extent is the Beveridge road the right road. To help us to answer this question, certain specific questions have been dealt with by the Committee in an Appendix which is attached. Many of them raise political questions of great difficulty and it has not been possible for us to reach agreement upon all of them. In particular, the Committee was divided on the proposed supersession of the Approved Societies and the future treatment of Workmen's Compensation. We have, however, indicated as far as possible where our views diverge and where they are unanimous. 200/B/3/2/C216/5/93